Penerapan Elektronik Pendapatan Asli Daerah (E-PAD) dalam Meninjau Penerimaan Pajak Daerah pada UPT BPKD Wilayah Cihaurbeuti - Salsabila, Fauziyah Latiefa; Hadiyan, Edwin (Budgeting: Jurnal Akuntansi Syariah, 2023)
The research aims to determine the application of the government accounting information system (electronic local revenue application/e-Pad) to the review of regional tax revenue at the UPT BPKD Ciheurbeuti Region. The research method use in this research is the qualitative method. The data sources used in this research are primary data and secondary data, then using field study and library research data collection techniques. The results of the research show that the UPT BPKD Office has imolemented an electronic application for local original income (E-Pad) with the benefits of a system for knowing the list of taxpayers, registering new taxpayers, determining taxes for raxpayers, registering tax bills for taxpayers, track record of taxpayer deposits, and also provide convenience to taxpayers in Ciamis Cihaurbeuti Regency. However, in its implementation there are still several concerns that must be addressed.